Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat di Kelurahan Klasuur - Dessy N. Waromi; Yanti Timisela; Agnes Eyne Banes (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of service quality on community satisfaction in the Klasuur Village. The data analysis method used is quantitative descriptive analysis. Significant test through (t-test), using simple linear regression and the coefficient of determination (R2). The population in this study is all people in the Klasuur Village. A sample of 98 respondents. Primary data obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 6,333 + 0.740X, the regression coefficient value of 0.740 means that every time there is a change and one percent addition to the service quality variable, the community satisfaction variable will increase equal to 0.740 if the service quality variable is zero, then community satisfaction has a value of 6,333. In the test the coefficient of determination obtained R square 52.4%. meaning that service quality affects community satisfaction by 52.4%. while the remaining 47.6% is influenced by other factors not analyzed in this study. The results of the t test, where tcount is 10.276 > from ttable 1.6652, it can be said that the service quality variable has a positive and significant effect on community satisfaction.